Contextual victimization is associated with slower inhibition control: A pictorial violence‐Stroop study carried out in Juárez, Mexico - Martin Del Campo Rios, Jaime (2020)
Contextual victims are those individuals who are indirectly traumatized by the physical and sociocultural conditions of their violent communities through second‐hand information. The purpose of this study was to examine the inhibitory control to violent stimuli in contextual victims from the city of Juárez, Mexico. A pictorial violence‐Stroop was constructed with violent, positive, and neutral images. Forty‐six university students with low (n = 22) and high (n = 24) scores on the Community Victimization by Community Violence Questionnaire participated. The study adopted a 2 (group = high contextual victims and low contextual victims) × 3 (stimulus type = violent, positive, and neutral) factorial design with repeated measures on the second factor. There were two signi cant e ffects which favored the low‐ context compared with the high‐context victimization group, notably faster reaction times in the violent stimulus condition (968.93 vs. 1136.26 ms; H = 5.031; p = .024) and the neutral stimulus condition (899.68 vs. 1013 ms; H = 5.130; p = .025). Results suggest that individuals who are highly exposed to contextual violence may be more sensitive towards violent stimuli, and that their performance on inhibitory tasks that include violence as a distractor cue may be more cognitively demanding.